A Study of the Buddhavaṃsa in the Theravāda Scriptures - Malad , Suwichai (BUDDHO, 2023)
This study aims to analyze the Buddhavaṃsa in the Theravāda scriptures, focusing on its content, structure, and religious significance. The Buddhavaṃsa is a part of the Khuddaka Nikāya in the Sutta Piṭaka, describing the biographies of 28 Buddhas, with particular emphasis on their perfections (pāramī) before attaining enlightenment. This research employs a documentary analysis method, referencing Pāli scriptures, commentarial explanations, and related scholarly studies. The findings reveal that the Buddhavaṃsa plays a crucial role in shaping beliefs about the Bodhisattva path and the concept of Buddhahood. Moreover, it serves as a means of transmitting religious ideals and reinforcing faith in Buddhism.